Library Users’ Satisfaction with Information Resources and Services at the University of Bamenda, Cameroon: Perspectives for Improvement in the Era of Transformative Education - Menyong , Bongnda Winifred Benedict Beriliy epse (Journal of Education and Practice, 2025)
Purpose: The purpose of the study was to find out the extent to which library users of The University of Bamenda, Cameroon, are satisfied with the library information resources and services offered and how these could be improved. Methodology: The convergent parallel mixed-methods research design was adopted and the data collection instrument was a structured questionnaire. The target population of the study was all lecturers and students who used the library of The University of Bamenda regularly. 220 responses were obtained through a simple random sampling technique. The quantitative data was analysed using frequency counts, percentages, means and standard deviations aided by SPSS version 25.0. Thematic approach was used to analyse the qualitative data. Findings: The findings revealed that library users of The University of Bamenda, Cameroon, are to a considerable extent satisfied with the information resources provided with an overall mean of 3.15. They are largely satisfied with services provided with an overall mean of 3.17. Library users suggested the need for expansion, modernization, and inclusivity. Recommendations: The study recommended an expansion in online databases, staff training programs, and collaboration with faculties to align acquisitions with academic needs.